Meningkatkan Kosakata Siswa Kelas Tujuh melalui Penerapan Teknik Pemetaan Pikiran - Herlianti; Aminah; Rofiqoh (Universitas Tadulako, 2022)
The objective of the research is to improve the students’ vocabulary through the implementation of mind mapping technique. This research was conducted by using classroom action research. Additionally, the data in this research were taken from 30 seventh grade students of SMPN 2 Ampana Kota. In collecting the data, the researcher used observation checklist for the students’ and the teacher’s performances, vocabulary test, and field notes. Vocabulary test was used as the main instrument, supported by observation and field notes as the supporting instruments. The result showed that there was improvement of the students’ scores on cycle II. The implementation of the two cycles showed the enriching of students’ achievement. In the test of cycle I, almost all students were failed. By changing the steps of the implementation of mind mapping technique, all students were successful. Additionally, most of the students’ scores in the cycle II belong to “very good category” and all of them are qualified to be “successful.” This is because the emphasis of using mother tongue when teaching mind mapping makes the students improve their vocabulary. In conclusion, the implementation of mind mapping technique improved the students’ vocabulary.